Costimulation of T-cell activation and virus production by B7 antigen on activated CD4+ T cells from human immunodeficiency virus type 1-infected donors. - Haffar, O K (1993)
Infection with the human immunodeficiency virus type 1 (HIV-1) requires T-cell activation. Recent studies have shown that interactions of the T-lymphocyte receptors CD28 and CTLA-4 with their counter receptor, B7, on antigen-presenting cells are required for optimal T-cell activation. Here we show that HIV-1 infection is associated with decreased expression of CD28 and increased expression of B7 on CD4+ T-cell lines generated from seropositive donors by alloantigen stimulation. Loss of CD28 expression was not seen on CD4+ T-cell lines from seronegative donors, but up-regulation of B7 expression was observed upon more prolonged culture. Both T-cell proliferation and interleukin 2 mRNA accumulation in HIV-1-infected cultures required costimulation with exogenous B7 because these events were blocked by CTLA4Ig, a soluble form of CTLA-4 that binds B7 with high avidity. In contrast, levels of HIV-1 RNA were not affected by CTLA4Ig, indicating that regulation of virus transcription in these cultures did not depend upon CD28-B7 engagement. Infected T cells could present alloantigen to fresh, uninfected CD4+ T cells, leading to increased proliferation and virus spread to the activated cells. Both of these events were blocked by CTLA4Ig. Thus, chronic activation of HIV-1-infected CD4+ T cells reduces expression of CD28 and increases expression of B7, thereby enabling these T cells to become antigen-presenting cells for uninfected CD4+ T cells; this might be another mechanism for HIV-1 transmission via T-cell-T-cell contact.